Family Literacy Development Strategy in Community Learning Center (CLC) Fatumation in The Liquica District of The Timor Leste Democratic Republic (RDTL) - Safuri Musa (Universitas Negeri Padang, 2020)
The Democratic Republic of East Timor as a newly independent country is faced with various problems in the field of education, including the family literacy program. The family as the smallest unit in social life needs to get the main attention in an effort to increase their dignity and with various programs that are directly able to empower it. One of the institutions that carried out the process was that which was carried out by CLC. This study aims to analyze the family literacy development strategy implemented by CLC Fatumasi. The research method used is qualitative, with participatory, ethnographic and collaborative research approaches. Data collection is done through observation, interviews, and documentation studies. The strategy taken is to implement eight steps, namely: identification of family literacy learning needs, the survey of resource potentials, priority scale analysis of learning needs, preparation of family literacy program design, preparation of family literacy curriculum, developing family literacy learning materials, application of family literacy learning, and follow up on family literacy development.Keywords: Family Literacy, Community Learning Center (CLC)